Renal cell carcinoma in a von Hippel-Lindau syndrome; when should pheochromocytoma be anticipated? - Mohd Shah, Azarisman Shah; K, Nor Azmi (Singapore Medical Association, 2007)
A 39-year-old man was diagnosed with von Hippel-Lindau syndrome, which was associated with retinal haemangioblastoma, cervical cord haemangioblastoma and bilateral renal cell carcinoma. He subsequently underwent an arterial embolisation and cervical laminectomy, following a spinal angiogram of the cervical lesion. He also had a right radical nephrectomy, with no perioperative complications. However, on admission for the left radical nephrectomy, he was noted to have preoperative hypertension. Further investigation revealed an enlarged left adrenal gland on abdominal computed tomography scan and raised urinary catecholamines. We discuss the risk of renal cell carcinoma a nd ph a e oc h romoc y toma a r i s ing concomitantly in von Hippel-Lindau syndrome, and how best to investigate and manage them.